2007
DOI: 10.21273/jashs.132.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ratio-based Responses

Abstract: It is not appropriate to compare ratio-based expressions for different cultivars or treatments if a plot of the denominator versus the numerator of a ratio-based expression has a nonzero y-intercept and the values for either the denominators or numerators differ with cultivars or treatments. Whenever nonzero y-intercepts are encountered, the value for a ratio-based expression will be dependent on both the denominator and numerator. The “ratio proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…This shows the complexity of anthocyanin accumulation in response to different environmental factors. In addition, more emphasis needs to be placed on separating out environmental influences from possible indirect responses of ratio-based expressions (proportional composition) that are influenced by denominator size (61). This idea of direct and indirect effects on proportional composition will be explored further in a separate paper.…”
Section: Resultsmentioning
confidence: 99%
“…This shows the complexity of anthocyanin accumulation in response to different environmental factors. In addition, more emphasis needs to be placed on separating out environmental influences from possible indirect responses of ratio-based expressions (proportional composition) that are influenced by denominator size (61). This idea of direct and indirect effects on proportional composition will be explored further in a separate paper.…”
Section: Resultsmentioning
confidence: 99%
“…We can thus conclude that the trend for lower 15 N : 14 N ratio in the smallest species is then an epiphenomenon of less total N uptake in comparison with the other species. Although tissue types appear to visually fall on different allometic regression lines in Figure 1a and b, no statistical differences in 15 N : 14 N ratio for tissue type were detected in a standard ANOVA (Table 1).…”
Section: Resultsmentioning
confidence: 73%
“…Studies where ratios lead to biased or even opposite conclusions than what a direct evaluation of the relationship between numerators and denominators reveal are well documented [5,[8][9][10][11][12][13][14]. Packard and Boardman [11] suggested that researchers avoid using ratios and use an analysis of covariance (ANCOVA) instead.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations